Attack on Chestnut-bellied Euphonia nestlings by army ants - Pizo, Marco A. [UNESP] (My University, 2000)
I report some observations of a Chestnut-bellied Euphonia (Euphonia pectoralis) nest in a lowland Atlantic Forest of southeastern Brazil during the early nestling period. During 7.5 hours of observations, the nest was attended 46.3% of the time, 45.6% by the female and 0.7% by the male. Unattended periods lasted 16-38 min. Parents visited the nest most of the time together at 36-59 min intervals. There were 1.06 feeding visits per nestling per hour. The two nestlings in the nest ended up preyed upon by army ants (Labidus praedator, Ecitoninae). The low height of the nest (0.8 m) may have facilitated its detection by the ants.
Keywords: ant; mortality; nestling; predation; Brazil; Euphonia pectoralis; Formicidae; Hymenoptera; Labidus praedator